Analgesics in pain management - Castañeda C., Benjamín (2022)
We have performed an inquiry in 692 drug stores ofLima in order to know the disposal of the differents analgesics utilized in pain treatment. We found that the 12% are drugs for the visceral pain treatment and 88% are drugs for soma tic pain treatment.Nonsteroidal anti-inflammatory drugs constitute the 68 % of total analgesics disposal while opiods are only the 5% of the total, and morphine only the 0,1% of all pharmacologycal analgesic groups.